Pengaruh Model Pembelajaran Discovery Learning Berbantuan Media Diorama Terhadap Hasil Belajar IPA Siswa Kelas V SD Negeri 20 Pulubala - Gita Sagita Nani; Abdul Haris Panai; Gamar Abdullah; Kudus; Isnanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Effect of the Discovery Learning Model Assisted by Diorama Media on Science Learning Outcomes of Fifth Grade Students at SD Negeri 20 Pulubala. Thesis. Department of Elementary Teacher Education. Faculty of Education. Universitas Negeri Gorontalo. The supervisor is Prof. Dr. Abdul Haris Panai, M.Pd., MCE and the co-supervisor is Dr. Gamar Abdullah, S.Si., M.Pd.The research question in this study is